2020
DOI: 10.1093/mnrasl/slaa044
|View full text |Cite
|
Sign up to set email alerts
|

ZTF J1901+5309: a 40.6-min orbital period eclipsing double white dwarf system

Abstract: The Zwicky Transient Facility has begun to discover binary systems with orbital periods that are less than 1 hr. Combined with dedicated follow-up systems, which allow for high-cadence photometry of these sources, systematic confirmation and characterization of these sources are now possible. Here, we report the discovery of ZTF J190125.42+530929.5, a 40.6 min orbital period, eclipsing double white-dwarf binary. Both photometric and spectroscopic modeling confirm its nature, yielding an estimated inclination o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
(48 reference statements)
0
27
0
Order By: Relevance
“…In this Letter, we report the discovery of ZTF J205515.98+465106.5 (hereafter ZTF J2055+4651), the second confirmed member of Roche lobe-filling hot subdwarf stars in compact binaries. ZTF J2055+4651 was discovered in a period search using the conditional entropy period-finding algorithm (Graham et al 2013) of all Pan-STARRS objects with colors of g−r<0.2 and r−i<0.2, and more than 50 ZTF measurements at the time, as described in Burdge et al (2019) and Coughlin et al (2020). Conditional entropy is an information-theory-based algorithm that seeks to find the period that produces the most ordered (lowest entropy) arrangement of data points in the phase-folded light curve while also accounting for the phase space coverage of the data.…”
Section: Introductionmentioning
confidence: 99%
“…In this Letter, we report the discovery of ZTF J205515.98+465106.5 (hereafter ZTF J2055+4651), the second confirmed member of Roche lobe-filling hot subdwarf stars in compact binaries. ZTF J2055+4651 was discovered in a period search using the conditional entropy period-finding algorithm (Graham et al 2013) of all Pan-STARRS objects with colors of g−r<0.2 and r−i<0.2, and more than 50 ZTF measurements at the time, as described in Burdge et al (2019) and Coughlin et al (2020). Conditional entropy is an information-theory-based algorithm that seeks to find the period that produces the most ordered (lowest entropy) arrangement of data points in the phase-folded light curve while also accounting for the phase space coverage of the data.…”
Section: Introductionmentioning
confidence: 99%
“…One way to prepare for LISA is by developing ground-and space-based instrumentation optimized to best characterize the optically detectable portion of its source population in an efficient manner. We hope that in this work, Burdge et al (2019aBurdge et al ( , 2019bBurdge et al ( , 2020, and Coughlin et al (2020), we have demonstrated that high-speed photometers, which can obtain densely sampled high-S/N light curves with high temporal resolution, will be one of the most powerful tools for such characterization. Such instruments on 10 and 30 m class telescopes could be used to characterize binaries like ZTF J2243+5242 and ZTF J1539+5027 to 10-30 kpc, distances well matched to LISAʼs sensitivity threshold.…”
Section: Implications For Lisa and The Vromentioning
confidence: 70%
“…These searches enable identification of populations of objects, such as cataclysmic variables (Szkody et al 2020), Be stars (Ngeow et al 2019), Cepheids and RR Lyrae, useful for studying the processes and properties of galaxy formation (Saha 1984(Saha , 1985Catelan 2009) and measuring the expansion rate of the Universe (Freedman et al 2001). In addition, they are also sensitive to rare objects, such as short-period white dwarf binaries (Burdge et al 2019a,b;Coughlin et al 2020), large-amplitude, radial-mode hot subdwarf pulsators (Kupfer et al 2019), and ultracompact hot subdwarf binaries (Kupfer et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To highlight one source class, we are discovering and characterizing the population of so-called ultra-compact binaries (UCBs), which have two stellar-mass compact objects with orbital periods P orb < 1 hour (Burdge et al 2019a,b;Coughlin et al 2020). Many of the UCBs emit gravitational waves in the milliHertz regime with sufficient strain for the upcoming Laser Interferometer Space Antenna (LISA) to detect (Amaro-Seoane et al 2017).…”
Section: Introductionmentioning
confidence: 99%